2021
DOI: 10.4102/jsava.v92i0.2120
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use practices of veterinarians and para-veterinarians and the implications for antibiotic stewardship in Nigeria

Abstract: The aim of this study was to describe the antibiotic use practices of veterinarians and para-veterinarians in Nigeria. An online survey was distributed during November through December 2018 via email and phone to veterinarians and para-veterinarians to collect information on antibiotic use practices. Data were downloaded into Excel and descriptive statistics were presented and analysed. The survey was completed by 390 respondents. Almost all respondents (98.5%, 384/390) recommended the use of antibiotics to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 39 publications
3
18
0
Order By: Relevance
“…Overall, 25.7% of our respondents displayed good attitude/prescribing behaviour towards AMS although some respondents declared that when in doubt they referred to the VF for information on the appropriate use of antimicrobials. This is in agreement with findings of a study done in South-eastern Nigeria [ 17 ] but not consistent with findings from another study among veterinary students where only 14% of respondents declared that they would consult the VF and also at variant with another study in Nigeria where only 9.3% of veterinary professionals referred to the VF [ 18 , 24 ]. Recent studies have reported the need to update the VF regularly for effective AMS in veterinary practice [ 20 ].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Overall, 25.7% of our respondents displayed good attitude/prescribing behaviour towards AMS although some respondents declared that when in doubt they referred to the VF for information on the appropriate use of antimicrobials. This is in agreement with findings of a study done in South-eastern Nigeria [ 17 ] but not consistent with findings from another study among veterinary students where only 14% of respondents declared that they would consult the VF and also at variant with another study in Nigeria where only 9.3% of veterinary professionals referred to the VF [ 18 , 24 ]. Recent studies have reported the need to update the VF regularly for effective AMS in veterinary practice [ 20 ].…”
Section: Discussionsupporting
confidence: 84%
“…Secondly, there is a possibility of selection bias as the veterinary register issued by the veterinary council of Nigeria was used to obtain a list of veterinarians in the study area. However some veterinarians who were active on social media with good internet access but not actively practicing in the veterinary industry may have participated in the survey and consistent with the literature [ 24 ].…”
Section: Discussionmentioning
confidence: 90%
“…A lack of policies regulating antimicrobial prescribing, dispensing and easy access to antimicrobials have been reported as reasons for inappropriate use in developing countries ( 7 – 11 ). The lack of therapeutic guidelines and veterinary legislative frameworks that guide veterinary service professionals have also been reported ( 5 , 9 , 11 – 14 ). Self-prescribing of antimicrobials by farmers has also been reported in developing countries ( 6 , 12 , 15 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that inappropriate use of an antibiotic may result in perceived ineffectiveness. In a previous study of animal health professionals in Nigeria, a high proportion of respondents recommended the use of antibiotics to manage non-bacterial pathogens, including viruses, protozoans, and even fungi [17]. Such indiscriminate use of antibiotics can exert selection pressure, allowing resistant strains to proliferate and lead to increased risk of AMR [18].…”
Section: Pharmaceutical Products 421 Antibioticsmentioning
confidence: 99%
“…In the current study, over a third (42.9%) of the respondents reported using enrofloxacin in the previous production cycle. Fluoroquinolones are categorised as critically important antimicrobials (CIAs) for human health [21,22], and there is concern that the use of enrofloxacin in animals could lead to sharing of genes encoding resistance to fluoroquinolones in people [17].…”
Section: Pharmaceutical Products 421 Antibioticsmentioning
confidence: 99%